2012
DOI: 10.1155/2012/940272
|View full text |Cite
|
Sign up to set email alerts
|

Angular Response of Magnetostrictive Thin Films

Abstract: The magnetostrictions of the single TbFe layer and coupled Py/TbFe2bilayers were measured by using laser deflectometry. The dependences of the magntostriction performance on the driving magnetic field direction have been investigated. The relationship studies between the saturation bending angle and torsion angle of the single layer with perpendicular anisotropy and coupled bilayers with in-plane uniaxial anisotropy have been conducted. Interesting “jump” reflecting the spin dynamics is observed in the magneto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…These results exhibit the similar trends to those reported by Ref. 20. In that work, the shape of the specimen was also rectangular, the same as ours; and the size (22×5×0.16 mm 3 ) was similar to ours.…”
Section: Effects Of Magnetic Field Strengths and Orientations On Deflsupporting
confidence: 91%
See 1 more Smart Citation
“…These results exhibit the similar trends to those reported by Ref. 20. In that work, the shape of the specimen was also rectangular, the same as ours; and the size (22×5×0.16 mm 3 ) was similar to ours.…”
Section: Effects Of Magnetic Field Strengths and Orientations On Deflsupporting
confidence: 91%
“…However, in Ref. 20, the deformation of the specimen was measured from both the long and the short directions. The results from the two directions showed that the deflections produced by magnetic field at different values of φ can be fitted by functions of cos 2 (φ) and sin 2 (φ), respectively.…”
Section: Effects Of Magnetic Field Strengths and Orientations On Deflmentioning
confidence: 99%
“…First to consider is why the deformation patterns were not symmetric with respect to the X-Y axes. There are at least 3 reasons: (a) the boundary conditions related to the mount will affect the shape changes; (b) the response of the Terfenol-D (T-D) is not isotropic; 4,10 and, the interaction between the EM induced stress and inherent stress from the T-D coating. At a minimum all of these effects can be calibrated and then taken into account in the implementation of a functional DM for wave front control.…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic smart material (MSM) films are usually deposited on substrates by an RF or DC magnetron sputtering method. The sputtering targets can be of a cast composite type or can consist of pure element sources [10][11][12][13][14][15][16]. By adjusting the sputtering parameters like argon pressure, bias voltage and power, the magnetostrictive strains are different even for the same target materials.…”
Section: Introductionmentioning
confidence: 99%